2021
DOI: 10.1136/annrheumdis-2021-220209
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome analysis identifies skin-specific T-cell responses in systemic sclerosis

Abstract: ObjectivesAlthough T cells have been implicated in the pathogenesis of systemic sclerosis (SSc), a comprehensive study of T-cell-mediated immune responses in the affected skin of patients with progressive SSc is lacking. Droplet-based single-cell transcriptome analysis of SSc skin biopsies opens avenues for dissecting patient-specific T-cell heterogeneity, providing a basis for identifying novel gene expression related to functional pathways associated with severity of SSc skin disease.MethodsSingle-cell RNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 57 publications
(67 reference statements)
0
35
0
Order By: Relevance
“…In a mouse model of salt-induced hypertension, Zhang et al showed that hypertensive vessels present increased smooth muscle cell populations, partly due to endothelial-to-mesenchymal cell transition [ 44 ]. In a context of systemic sclerosis, single-cell sequencing was used to study immune cell heterogeneity between patients and healthy controls using skin samples [ 45 ], or whole endothelial cell genetic patterns in individuals with or without the disease [ 46 ]. Such investigations would be of particular interest in blood vessels from SRC patients to identify the consequences of SRC-IgG on specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of salt-induced hypertension, Zhang et al showed that hypertensive vessels present increased smooth muscle cell populations, partly due to endothelial-to-mesenchymal cell transition [ 44 ]. In a context of systemic sclerosis, single-cell sequencing was used to study immune cell heterogeneity between patients and healthy controls using skin samples [ 45 ], or whole endothelial cell genetic patterns in individuals with or without the disease [ 46 ]. Such investigations would be of particular interest in blood vessels from SRC patients to identify the consequences of SRC-IgG on specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The receptors of γΎ T cell are Îł chain and ÎŽ chain which permit recognition of antigens without MHC restriction. In addition, a new subset of T cells in SSc skin likely promoting B-cell responses has been fully revealed by scRNA-seq which provides a fuller framework for understanding the contribution of T lymphocytes to autoimmunity (Gaydosik et al, 2021).…”
Section: T Lymphocytesmentioning
confidence: 99%
“…In this study, CXCL13 + T cells were adjacent to CD20 + B cells and expressed Tfh-related genes with lower levels like ICOS and PD1 but not BCL6 and CXCR5. Therefore, it may be a special Tfh subset, and treatment for CXCL13 + T cells may prevent disease progression (Gaydosik et al, 2021) (Figure 2).…”
Section: T-cell Subsets By Scrna-seqmentioning
confidence: 99%
“…Several T-lymphocyte subsets and associated cytokines have been implicated in the inflammatory and fibrotic processes of SSc, however their heterogeneity in SSc skin has only recently been revealed by Gaydosik et al ( 95 ). They detected several subsets of infiltrating, as well as tissue-resident T-lymphocytes in healthy and SSc skin that were enriched in different signaling pathways.…”
Section: Application Of Scrna-seq In Autoimmune Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…A significantly lower frequency of CD3 + CXCL13 + cells was detected in SSc patients treated with immunosuppressive drugs, compared with untreated patients. This indicates that a more targeted T cell-based therapy might be used in SSc patients, resulting in an improved efficacy and lower toxicity ( 95 ).…”
Section: Application Of Scrna-seq In Autoimmune Inflammatory Rheumatic Diseasesmentioning
confidence: 99%